"Timeless People": The Development of the Ancestral Figure in Three Novels by Alice Walker - Heczková, Jana (Current Objectives of Postgraduate American Studies, 2012)
The concept of the ancestral figure is one of the important aspects of African American literature. The paper traces the development of the concept in three novels by Alice Walker, concentrating mainly on the imagery Walker employs for the personification of the ancestral.